Integration of Non Alcoholic Fatty Liver Diseases (NAFLD) into NPCDCS programme: A recent initiative in India - Srivastava, Prerna; Prasad, Manya; Kapil, Umesh (Indian Journal of Community Health, 2022)
Non-alcoholic fatty liver disease (NAFLD) is an emerging public health problem globally. NAFLD is one of the most common liver diseases worldwide and is the most common cause of abnormal liver enzymes in many developed countries. NAFLD is estimated to afflict approximately 1 billion individuals worldwide. An estimated 20-30 % of general population is afflicted from it globally. In India NAFLD could be a silent epidemic with its prevalence ranging from 9-32%. Studies have shown, strong association of NAFLD with major Non Communicable diseases (NCD) like Diabetes, Obesity, CVD, Chronic Kidney diseases, Cancers, etc. Perceiving the threat of NAFLD and the central role of hepatic accumulation of fat in the pathogenesis of other NCD, the Government of India (GoI) has taken steps to include NAFLD in the public health agenda. It has included it in the national NCD programme, i.e., National Programme for Prevention and Control of Cancer, Diabetes, Cardiovascular Diseases and Stroke (NPCDCS) in 2021. India has become the first country in the world to start a national programme for preventive efforts for NAFLD. The present review describes public health relevance of NAFLD and the process of integration of Non Alcoholic Fatty Liver Diseases (NAFLD) into NPCDCS programme in India.